Manufacturing method of degradable regenerated cellulose hand tearing tape

By cold stacking and embrittlement treatment of the regenerated cellulose trademark belt, the problems of non-hand tearing and non-degradable are solved, and the easy tearing and ecological and environmental protection of the trademark belt is achieved, which significantly improves the biodegradation speed, improves user experience and environmental protection. performance.

CN119243468AInactive Publication Date: 2025-01-03ZHEJIANG KING LABLE TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411786110.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing trademark belts cannot be tear-down and cannot be degraded, affecting the user experience and ecological and environmental protection.

Method used

Using regenerated cellulose as yarn, a degradable hand-teared trademark tape was prepared by cold stack pretreat, embrittlement and shaping. The cold reactor treatment solution contains sodium hydroxide, fatty alcohol polyoxyethylene ether and sodium percarbonate, and the embrittlement treatment solution contains citric acid, zinc chloride and sodium phosphate, which destroy the molecular structure of the cellulose and promote degradation respectively.

Benefits of technology

It realizes the easy tear and degradation of the trademark belt, reduces the complexity of the process, has the characteristics of ecological and environmental protection, energy conservation and emission reduction, improves the user experience and significantly improves the speed of biodegradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of textile label tapes, and particularly relates to a manufacturing method of a degradable regenerated cellulose hand-tearing tape, which is characterized in that the easily degradable hand-tearing label tape is obtained by carrying out cold-batch pretreatment, embrittlement treatment and shaping treatment on a regenerated cellulose woven fabric. The core process of the method does not need acid-base or alcohol-base repeated treatment, compared with an existing treatment process, the complexity of the process is greatly reduced, and the method has the advantages of being ecological, environmentally friendly, capable of saving energy, reducing emission and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of textile trademark tapes, in particular to a method for manufacturing a degradable regenerated cellulose hand-tear tape. Background Art

[0002] As an important carrier of textile information, trademark tapes are mainly used in clothing, shoes, hats, bedding, toys and other industries to provide consumers with basic product attributes and performance. The trademark tape is woven into a strip continuously during production. Each small piece of fabric has logos such as the brand name, manufacturer, country name, and specifications. The size can be determined according to needs. At present, it is mainly prepared by embroidery, weaving and printing. Therefore, the trademark tape needs to meet specific functional requirements such as hand feel and printing. Among them, the printing method usually uses a certain type of fabric as the base fabric, and then it is coated and processed in the later stage such as calendering and striping to obtain the trademark cloth. Compared with the traditional weaving method, this method has high production efficiency and low cost.

[0003] There are also many disadvantages in the use of trademark tapes. For example, when the garments of foreign trade orders are sent abroad, the labels need to be changed, which is very troublesome. If the manufacturer sews multiple national labels, it will not only be bloated, but also not easy to wear. Some consumers with sensitive skin think that trademark tapes have an itchy effect on the skin. Therefore, in order to improve such user experience, we need to develop trademark cloth products that are easy to tear and remove.

[0004] Chinese patent CN115110312B provides a method for processing bio-based PTT fiber fabrics that can be used as base fabrics for trademark cloths, including the following steps: subjecting the bio-based PTT fiber fabrics to cold stacking treatment; subjecting the cold stacked fabrics to a whitening and brittle one-bath process in a flat width manner; and subjecting the whitening and brittle fabrics to a finalizing heat treatment. However, the trademark tape prepared by this method is a chemical fiber hand-tear tape that is not completely biodegradable and is not conducive to ecological protection. Therefore, a degradable hand-tear trademark tape is urgently needed. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for producing a degradable regenerated cellulose hand-tear tape, which solves the problems of the trademark tape being non-tearable and not easy to degrade, and the provided processing method is easy to operate, simple in process, low in energy consumption, and has the characteristics of being ecologically friendly, energy-saving and emission-reducing.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: The present invention provides a method for making a degradable regenerated cellulose hand-tearable tape, comprising the following steps: (1) Weaving: Select regenerated cellulose as yarn, design weaving pattern, yarn count, density, etc. to manufacture regenerated cellulose fabrics; (2) Cold stacking pretreatment: The fabric enters the cold stacking liquid coating machine in a flat width manner and is immersed in the cold stacking treatment liquid. The speed is 10-30 m / min, the temperature is 80-120 °C, the rolling pressure is 0.30-0.40 MPa, and the tension frame pressure is 0.35-0.45 MPa. After being immersed in the cold stacking treatment liquid, the fabric is coated with an outer layer in a roll-shaped manner, and the reel rotates at a speed of 280-300 rpm and is placed at room temperature for 24-36 hours. (3) Brittleness treatment: The pretreated regenerated cellulose fabric is brittle-treated in a roll-shaped manner on a dyeing machine at a speed of 80-100 m / min. The brittle treatment liquid in the dyeing machine is first heated to 60-80°C, kept warm for 1-3 times, and then heated to 120-140°C, with a pressure of 0.15-0.25 MPa, and kept warm for 3-6 times; after the heat preservation treatment, the temperature is lowered to 100°C and all the liquid is discharged, and then water is added, the temperature is raised to 95-100°C, and the water is discharged after one wash. The washing process is repeated 3-5 times; (4) Forming treatment: The embrittled fabric is fed into the forming machine in a flat width manner at a speed of 10 to 30 m / min and a temperature of 180 to 200 °C.

[0007] Furthermore, in step (1), the regenerated cellulose yarn can be one of Tencel, viscose, bamboo fiber, modal, Incel and Spira, the weaving texture is one of plain, satin and twill, the yarn count is 10-120S / 1, and the fabric density is 100-120g / m2.

[0008] Furthermore, the regenerated cellulose fabric in step (1) is composed of cellulose fibers in both warp and weft directions, and the radial tear strength of the fabric is 10 to 25N, and the weft tear strength is 10 to 25N.

[0009] Furthermore, the cold stack treatment liquid in step (2) comprises 1% to 2% sodium hydroxide, 4 to 7 g / L fatty alcohol polyoxyethylene ether, and 5 to 10 g / L sodium percarbonate.

[0010] Furthermore, the composition of the embrittlement treatment liquid in step (3) is 3-6 mol / L citric acid, 10-15 g / L zinc chloride, and 10-30 g / L sodium phosphate.

[0011] In the present invention, the fabric made of regenerated cellulose is subjected to brittle damage treatment, which mainly includes cold stack pretreatment and embrittlement treatment. The cold stack treatment liquid includes sodium hydroxide, fatty alcohol polyoxyethylene ether and sodium percarbonate, and the embrittlement treatment liquid includes citric acid, zinc chloride and sodium phosphate. Fatty alcohol polyoxyethylene ether is a non-ionic penetrant that can reduce the surface tension of the liquid. Therefore, during the cold stack treatment process, fatty alcohol polyoxyethylene ether can enable the treatment liquid to quickly and evenly impregnate between the fabric fibers and diffuse between the warp and weft fibers of the fabric to ensure the uniformity of the treatment effect and avoid the situation where local treatment is not in place. Sodium hydroxide can cause cellulose fibers to swell, destroy some hydrogen bonds between cellulose molecules, and make the internal structure of the fibers relatively loose. This structural change increases the contact area between cellulose and the treatment liquid, which is beneficial to the degradation reaction in the subsequent embrittlement treatment process; at the same time, sodium hydroxide will also react with the hydroxyl groups in the cellulose molecules to reduce the crystallinity of the fibers, which also creates favorable conditions for the subsequent embrittlement treatment. Sodium percarbonate decomposes in the treatment solution to produce hydrogen peroxide, which can oxidize some hydroxyl groups on the cellulose molecular chain and convert them into aldehyde or carboxyl groups that are more easily hydrolyzed. These oxidized groups are more likely to break chemical bonds under the action of acid during the subsequent embrittlement treatment process, thereby promoting the degradation of the fabric. The basic structural unit of regenerated cellulose is glucose, and its molecular chain is connected by glucose through glycosidic bonds. The citric acid in the embrittlement treatment solution can undergo hydrolysis reaction with the glycosidic bonds in the cellulose molecular chain. Under high temperature and high pressure conditions, citric acid can penetrate into the interior of cellulose and gradually destroy its molecular structure. A large number of glycosidic bonds are broken, which reduces the degree of polymerization of cellulose. As the degree of polymerization decreases, the strength of the fabric decreases, and it becomes easier to tear by hand and degrade. Zinc chloride, as a catalyst in the embrittlement treatment, can reduce the activation energy of the acid hydrolysis reaction and accelerate the reaction rate of hydrochloric acid and glycosidic bonds. It promotes the cellulose molecular chain to break faster under relatively mild conditions, enhancing the embrittlement and degradation effects of the fabric. Sodium phosphate, as a buffer, helps maintain the pH value of the embrittlement treatment solution within an appropriate range. The stable pH environment ensures that the acid hydrolysis reaction can proceed continuously and stably, avoiding abnormal or termination of the reaction due to drastic changes in pH value, which is beneficial to the continuous degradation of the fabric.

[0012] The beneficial effects of the present invention are: The present invention provides a method for making a degradable regenerated cellulose hand-tearable tape, wherein the degradable hand-tearable label tape is obtained by performing cold stacking pretreatment, embrittlement treatment and shaping treatment on a regenerated cellulose woven fabric. The core process of the present invention does not require repeated acid-base or alcohol-base treatment, and compared with the existing treatment process, the complexity of the process is greatly reduced. DETAILED DESCRIPTION

[0013] The present invention is further described below in conjunction with the examples, but the present invention is not limited thereby. The experimental methods in the following examples are conventional methods unless otherwise specified.

[0014] Example 1 A method for making a degradable regenerated cellulose hand-tearable tape comprises the following steps: (1) Weaving: Tencel is used as the yarn, the weaving pattern is plain, the yarn count is 10S / 1, the fabric density is 100g / m2, the radial tear strength is 10N, and the weft tear strength is 10N; (2) Cold stacking pretreatment: The fabric enters the cold stacking liquid coating machine in a flat width manner and is immersed in the cold stacking treatment liquid. The speed is 10 m / min, the temperature is 80 °C, the rolling pressure is 0.30 MPa, and the tension frame pressure is 0.35 MPa. After being dipped in the cold stacking treatment liquid containing 1% sodium hydroxide, 4 g / L fatty alcohol polyoxyethylene ether, and 5 g / L sodium percarbonate, the fabric is coated with an outer layer in a roll-like manner, and the reel rotates at a speed of 280 rpm and is placed at room temperature for 24 h. (3) Embrittling treatment: The pretreated regenerated cellulose fabric was subjected to embrittlement treatment in a roll-shaped manner on a dyeing machine at a speed of 80 m / min. The embrittlement treatment liquid containing 3 mol / L citric acid, 10 g / L zinc chloride, and 10 g / L sodium phosphate in the dyeing machine was first heated to 60°C, kept warm for one pass, and then heated to 120°C with a pressure of 0.15 MPa and kept warm for three passes; after the heat preservation treatment, the temperature was lowered to 100°C and all the liquid was discharged, and then water was added, the temperature was raised to 95°C, and the water was discharged after one wash. The washing process was repeated three times; (4) Forming treatment: The embrittled fabric is fed into the forming machine in a flat width manner at a speed of 10 m / min and a temperature of 180 °C.

[0015] Example 2 A method for making a degradable regenerated cellulose hand-tearable tape comprises the following steps: (1) Weaving: bamboo fiber is used as yarn, the weaving pattern is satin, the yarn count is 120S / 1, the fabric density is 120g / m2, the radial tear strength of the fabric is 25N, and the weft tear strength is 25N; (2) Cold stacking pretreatment: The fabric enters the cold stacking liquid coating machine in a flat width manner and is immersed in the cold stacking treatment liquid. The speed is 30 m / min, the temperature is 120 °C, the rolling pressure is 0.40 MPa, and the tension frame pressure is 0.45 MPa. After being dipped in the cold stacking treatment liquid containing 2% sodium hydroxide, 7 g / L fatty alcohol polyoxyethylene ether, and 10 g / L sodium percarbonate, the fabric is coated with an outer layer in a roll-like manner, and the reel rotates at a speed of 300 rpm and is placed at room temperature for 36 hours; (3) Embrittling treatment: The pretreated regenerated cellulose fabric was subjected to embrittlement treatment in a roll-shaped manner on a dyeing machine at a speed of 100 m / min. The embrittlement treatment liquid containing 6 mol / L citric acid, 15 g / L zinc chloride, and 30 g / L sodium phosphate in the dyeing machine was first heated to 80°C and kept warm for 3 times, then heated to 140°C with a pressure of 0.25 MPa and kept warm for 6 times; after the heat preservation treatment, the temperature was lowered to 100°C and all the liquid was discharged, then water was added, the temperature was raised to 100°C, and the water was discharged after 1 wash. The washing process was repeated 5 times; (4) Forming treatment: The embrittled fabric is fed into the forming machine in a flat width manner at a speed of 30 m / min and a temperature of 200 °C.

[0016] Example 3 A method for making a degradable regenerated cellulose hand-tearable tape comprises the following steps: (1) Weaving: Modal is used as the yarn, the weaving pattern is twill, the yarn count is 10-120S / 1, the fabric density is 110g / m2, the radial tear strength of the fabric is 18N, and the weft tear strength is 18N; (2) Cold stacking pretreatment: The fabric enters the cold stacking liquid coating machine in a flat width manner and is immersed in the cold stacking treatment liquid. The speed is 20 m / min, the temperature is 1000 °C, the rolling pressure is 0.35 MPa, and the tension frame pressure is 0.40 MPa. After being dipped in the cold stacking treatment liquid containing 1.5% sodium hydroxide, 5.5 g / L fatty alcohol polyoxyethylene ether, and 7.5 g / L sodium percarbonate, the fabric is coated with an outer layer in a roll-like manner, and the reel rotates at a speed of 290 rpm and is placed at room temperature for 30 h. (3) Embrittling treatment: The pretreated regenerated cellulose fabric was subjected to embrittlement treatment in a roll-shaped manner on a dyeing machine at a speed of 90 m / min. The embrittlement treatment liquid containing 4.5 mol / L citric acid, 12.5 g / L zinc chloride, and 20 g / L sodium phosphate in the dyeing machine was first heated to 70°C and kept warm for 2 times, then heated to 130°C with a pressure of 0.20 MPa and kept warm for 5 times; after the heat preservation treatment, the temperature was lowered to 100°C and all the liquid was discharged, and then water was added and the temperature was raised to 98°C. After 1 wash, the water was discharged and the washing process was repeated 4 times; (4) Forming treatment: The embrittled fabric is fed into the forming machine in a flat width manner at a speed of 20 m / min and a temperature of 190 °C.

[0017] Comparative Example 1: This comparative example 1 is basically the same as Example 3, except that the cold stack pretreatment in step (2) is omitted.

[0018] Comparative Example 2: This comparative example 2 is basically the same as Example 3, except that there is no embrittlement treatment in step (3).

[0019] Test experiment: Five fabrics of Examples 1 to 3 and Comparative Examples 1 to 2 were used as test samples for testing.

[0020] 1. The tear strength was tested in accordance with GB / T3917.1-2009 “Tear properties of textile fabrics - Part 1: Determination of tear strength by impact pendulum method”. The results are shown in Table 1 below.

[0021] 2. The biodegradation time of the samples was tested according to the method of ASTM D3826-91, and the percentage (%) of the increase in degradation rate compared with the fabric that was not brittle treated was shown in Table 1 below.

[0022] Table 1 Performance test results As shown in Table 1, the warp tear strength of the fabrics treated in Examples 1 to 3 is less than 4.4N, and the weft tear strength is less than 4.7N, which shows a good tearing effect; while the tearing force of Comparative Example 1 is greater than that of the embodiment due to the lack of cold stack pretreatment and the lack of embrittlement treatment in Comparative Example 2. The samples of the embodiments all have excellent biodegradability, and their degradation rate is at least 60% higher than that of the fabrics that have not been embrittled, and the optimal degradation rate is increased to 71%; and the degradation rate of the embodiment is better than that of the comparative example by 29% to 32%. This shows that the implementation method provided in the present invention can more effectively reduce the tearing force of the fabric and increase the degradation rate of the fabric.

[0023] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for making a degradable regenerated cellulose hand-tearable tape, characterized in that: The following steps are involved: (1) Weaving: Select regenerated cellulose as yarn, design weaving pattern, yarn count, density, etc. to manufacture regenerated cellulose fabrics; (2) Cold stacking pretreatment: The fabric enters the cold stacking liquid coating machine in a flat width manner and is immersed in the cold stacking treatment liquid. The speed is 10-30 m / min, the temperature is 80-120 °C, the rolling pressure is 0.30-0.40 MPa, and the tension frame pressure is 0.35-0.45 MPa. After being immersed in the cold stacking treatment liquid, the fabric is coated with an outer layer in a roll-shaped manner, and the reel rotates at a speed of 280-300 rpm and is placed at room temperature for 24-36 hours. (3) Brittleness treatment: The pretreated regenerated cellulose fabric is brittle-treated in a roll-shaped manner on a dyeing machine at a speed of 80-100 m / min. The brittle treatment liquid in the dyeing machine is first heated to 60-80°C, kept warm for 1-3 times, and then heated to 120-140°C, with a pressure of 0.15-0.25 MPa, and kept warm for 3-6 times; after the heat preservation treatment, the temperature is lowered to 100°C and all the liquid is discharged, and then water is added, the temperature is raised to 95-100°C, and the water is discharged after one wash. The washing process is repeated 3-5 times; (4) Forming treatment: The embrittled fabric is fed into the forming machine in a flat width manner at a speed of 10 to 30 m / min and a temperature of 180 to 200 °C.

2. The method for making a degradable regenerated cellulose hand-tearable tape according to claim 1, characterized in that: In the step (1), the regenerated cellulose yarn can be one of tencel, viscose, bamboo fiber, modal, incel and spore, the weaving pattern is one of plain, satin and twill, the yarn count is 10-120S / 1, and the fabric density is 100-120g / m2.

3. The method for making a degradable regenerated cellulose hand-tearable tape according to claim 1, characterized in that: The regenerated cellulose fabric in step (1) is composed of cellulose fibers in both warp and weft directions, and the radial tear strength of the fabric is 10-25N, and the weft tear strength is 10-25N.

4. The method for making a degradable regenerated cellulose hand-tearable tape according to claim 1, characterized in that: The cold stack treatment liquid in step (2) comprises 1% to 2% sodium hydroxide, 4 to 7 g / L fatty alcohol polyoxyethylene ether, and 5 to 10 g / L sodium percarbonate.

5. The method for making a degradable regenerated cellulose hand-tearable tape according to claim 1, characterized in that: The ingredients of the embrittlement treatment liquid in step (3) are 3-6 mol / L citric acid, 10-15 g / L zinc chloride, and 10-30 g / L sodium phosphate.

Citation Information

Patent Citations

  • Pressurizing, scouring and bleaching one-bath process for obtaining high-whiteness cotton

    CN102965905A

  • Bamboo fiber label tape and production method thereof

    CN103590255A

  • Brand cloth easy to tear and manufacturing method thereof

    CN104532567A

  • Preparation method of high-temperature-resistant gas-sensitive material

    CN110208462A

  • Processing method of bio-based PTT (polytrimethylene terephthalate) fiber fabric capable of serving as base cloth for trademark cloth

    CN115110312A